Faktor - Faktor Penyebab Waste Material pada Proyek Peningkatan Jalan dengan Cor Beton, Kec. Bayung Lencir - Handayani, Elvira; Setiawan, Ari; Riananda, Agif (Jurnal Talenta Sipil, 2025)
Waste is a form of inefficiency and waste that arises from waiting time, materials, Human Resources, construction implementation, management, design and documentation, and external factors. This research aims to determine the factors causing high material waste in road improvement projects in Musi Banyuasin by taking samples at the construction project site. In analyzing the factors that cause material waste, there are several ways to find out, namely the data collection method in this research uses a questionnaire, while the analysis method uses the Descriptive Mean and the Borda method. This research shows that the waste that most often occurs in road improvement projects is external. Meanwhile, the waste variable that has the biggest impact on the project is soil type with a score of 510 using the Borda method calculation and 3.59 using the mean calculation.